2020
DOI: 10.1186/s12906-020-03040-0
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Zika virus activity and chemical characterization by ultra-high performance liquid chromatography (UPLC-DAD-UV-MS) of ethanol extracts in Tecoma species

Abstract: Background Plant species from the genus Tecoma are found in tropical and subtropical regions around the world. Some of them are grown as ornamental plants and others can be used as medicinal plants. In the present study, ethanolic extracts from trunks and leaves of Tecoma species were tested in vitro using assays against the Zika virus. Methods There was a total of 8 extracts obtained from different a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…quinquefasciatus (Hari & Mathew, 2018). In another axis, ethanolic extract, ethyl acetate, and aqueous fractions from Tecoma species leaves, exhibited potent in vitro antiviral activity against the Zika virus (Reis et al, 2020). Ovicidal activity and oviposition deterrence efficiency of aqueous leaf extracts of T. stans were reported on Ae.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…quinquefasciatus (Hari & Mathew, 2018). In another axis, ethanolic extract, ethyl acetate, and aqueous fractions from Tecoma species leaves, exhibited potent in vitro antiviral activity against the Zika virus (Reis et al, 2020). Ovicidal activity and oviposition deterrence efficiency of aqueous leaf extracts of T. stans were reported on Ae.…”
Section: Discussionmentioning
confidence: 99%
“…To assess T. stans extracts as safer and effective mosquitocides, several studies were undertaken on its repellent potential (Gupta & Gupta, 2020). Recently, Reis et al (2020) demonstrated its potential against an infectious mosquito‐borne flavivirus (Zika). Previously, some T. stans extracts were tested on mosquitoes, such as the effectiveness of petroleum ether extract on Ae.…”
Section: Introductionmentioning
confidence: 99%
“…Citrox, which is derived from citrus fruits, is composed of soluble bioflavonoids and hydroxylated phenolic structures produced by plants. Bioflavonoids have demonstrated their capacity to act against bacteria, fungi, and viruses ( Hooper et al 2011 ; Lalani et al 2020 ; Reis et al 2020 ; Zou et al 2020 ).…”
Section: Mouth Rinse Reagents With In Silico Anti–sars-cov-2 Activitymentioning
confidence: 99%
“…The Ministry of Health in Brazil has reported 579 new ZIKV cases between December 2019 and February 2020 [ 9 , 10 ]. First identified in Uganda in 1947 from rhesus monkeys, the ZIKV, particularly vectored by the yellow fever mosquito, Aedes aegypti , is a flavivirus originating from the Flaviviridae family [ 11 ]. The virus can be transmitted sexually, via blood transfusions, via organ transportation and from pregnant women to their fetuses [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Crenatoside identified from Tecoma stans var. stans displayed better anti-ZIKV activity (EC50: 34.78 µM) than the positive control ribavirin (EC50: 386.84 µM) [ 11 ]. Lipophilic ethers from citrus fruits present the ability to selectively inhibit ZIKV replication in human breast carcinoma (4T1) cells [ 17 ].…”
Section: Introductionmentioning
confidence: 99%